Reduced Prefrontal Short—Latency Afferent Inhibition in Older Adults and Its Relation to Executive Function: A TMS-EEG Study - Noda, Yoshihiro; Zomorrodi, Reza; Backhouse, Felicity; Cash, Robin F. H.; Barr, Mera S.; Rajji, Tarek K.; Chen, Robert; Daskalakis, Zafiris J.; Blumberger, Daniel M. (Frontiers in Aging Neuroscience, 2017)
Combining transcranial magnetic stimulation (TMS) with electroencephalography (EEG) allows for the assessment of various neurophysiological processes in the human cortex. One of these paradigms, short–latency afferent inhibition (SAI), is thought to be a sensitive measure of cholinergic activity. In a previous study, we demonstrated the temporal pattern of this paradigm from both the motor (M1) and dorsolateral prefrontal cortex (DLPFC) using simultaneous TMS–EEG recording. The SAI paradigm led to marked modulations at N100. In this study, we aimed to investigate the age-related effects on TMS-evoked potentials (TEPs) with the SAI from M1 and the DLPFC in younger (18-59 years old) and older (≥ 60 years old) participants. Older participants showed significantly lower N100 modulation in M1–SAI as well as DLPFC–SAI compared to the younger participants. Furthermore, the modulation of N100 by DLPFC–SAI in the older participants correlated with executive function as measured with the Trail making test. This paradigm has the potential to non-invasively identify cholinergic changes in cortical regions related to cognition in older participants.